Research progress on the roles of actin-depolymerizing factor in plant stress responses - Sun, Yongwang; Shi, Mengmeng; Wang, Deying; Gong, Yujie; Sha, Qi; Lv, Peng; Yang, Jing; Chu, Pengfei; Guo, Shangjing (Frontiers in Plant Science, 2023)
Actin-depolymerizing factors (ADFs) are highly conserved small-molecule actin-binding proteins found throughout eukaryotic cells. In land plants, ADFs form a small gene family that displays functional redundancy despite variations among its individual members. ADF can bind to actin monomers or polymerized microfilaments and regulate dynamic changes in the cytoskeletal framework through specialized biochemical activities, such as severing, depolymerizing, and bundling. The involvement of ADFs in modulating the microfilaments' dynamic changes has significant implications for various physiological processes, including plant growth, development, and stress response. The current body of research has greatly advanced our comprehension of the involvement of ADFs in the regulation of plant responses to both biotic and abiotic stresses, particularly with respect to the molecular regulatory mechanisms that govern ADF activity during the transmission of stress signals. Stress has the capacity to directly modify the transcription levels of ADF genes, as well as indirectly regulate their expression through transcription factors such as MYB, C-repeat binding factors, ABF, and 14-3-3 proteins. Furthermore, apart from their role in regulating actin dynamics, ADFs possess the ability to modulate the stress response by influencing downstream genes associated with pathogen resistance and abiotic stress response. This paper provides a comprehensive overview of the current advancements in plant ADF gene research and suggests that the identification of plant ADF family genes across a broader spectrum, thorough analysis of ADF gene regulation in stress resistance of plants, and manipulation of ADF genes through genome-editing techniques to enhance plant stress resistance are crucial avenues for future investigation in this field.